Hospital Standardized Mortality Ratio Is a Useful Burning Platform - Catherine Zahn, Michael Baker, John MacNaughton, Cara Flemming and Robert Bell (HealthcarePapers, 2008)
Hospital Standardized Mortality Ratio (HSMR) is an important indicator of hospital performance that can be immediately used by quality improvement teams. As described by Penfold et al., the indicator is not perfect. However, it does serve as a useful measure that is readily understood by healthcare professionals and the public. Engaging hospital staff in quality improvement work can be challenging and requires understandable quality measures. The Canadian Institute for Healthcare Information deserves our thanks for making this indicator available.